Correlation between pulsatility index of medial cerebri artery and cognitive function in patients with diabetes mellitus type 2 - Johannes, Herdy; Tumewah, Rizal; Sekeon, Sekplin A. S. (International Journal of Research in Medical Sciences, 2020)
Background: Cognitive impairment is prevalent among cerebrovascular disease (CVD). Diabetes mellitus type 2 (DMT2) is a major risk factor of CVD. Gold standard used for diagnosing vascular cognitive impairment (VCI) required a combination of neurophysiological approach and magnetic resonance imaging (MRI). The Neurosonological approach, involving measuring the pulsatility index (PI) of the middle cerebral artery (MCA) using Trans Cranial Doppler (TCD) could be applied as an affordable alternative to predict VCI. The objective of this study was to revealed the correlation between PI MCS and cognitive function among DMT2 patients. Methods: This study was a cross-sectional survey in patients with DMT2 visiting Neurology and Endocrine Outpatient Clinics at Prof. Dr. R. D. Kandou Manado General Hospital, who meet the inclusion and exclusion criteria. Sixty (60) subjects were examined by TCD with 2 MHz to assess the hypo-perfusion level. Their cognitive were assessed with the Indonesian version of Montreal Cognitive Assessment (MoCa-Ina). Results: Right and left MCA median PI was 1.1 (IQR 0.9-1.4) and 1.0 (IQR 0.9-1.2) consecutively. MoCa-Ina median score was approximately 25 (IQR 22-26). Boxplot graph showed left PI MCA median score was higher in patients with normal cognitive function compared with cognitive impairment. Authors could not reach any significant statistical difference between PI MCA score and its correlation with cognitive function (p>0.05). Conclusions: Majority of patients with DMT2 have PI MCA score within normal range. Cognitive function among patient with DMT2 was mostly impaired. There is no correlation between PI MCA with cognitive function of patients with DMT2.